Implementation of an IoT-based System for Monitoring Parameters and Tracking Transport Vehicles - Huynh, Nguyen Bao Phuong; Nguyen, Duy Thong (Journal of Technical Education Science, 2024)
The integration of Internet of Things (IoT) technology in vehicle monitoring systems has emerged as a promising solution for enhancing the efficiency, safety, and sustainability of transportation. Especially in refrigerated trucks, which transport fresh goods, monitoring parameters in the vehicle plays an important role in ensuring the quality of transported goods. These parameters can be monitored directly on the vehicle by the driver and at the same time, the manager needs to monitor remotely. This paper will present an IoT-based system to monitor critical parameters of vehicles, including temperature, humidity, fuel consumption, and positioning. The proposed system integrates a network of sensors within the vehicle to capture real-time data, which is transmitted to a centralized control unit for analysis and visualization. Through experiments, the effectiveness and reliability of the proposed system in providing accurate and timely information on vehicle parameters are demonstrated. The results highlight the potential of IoT solutions to revolutionize vehicle monitoring and management, bringing benefits and reducing costs in the transportation sector. Moreover, a discussion on the future trends and solutions in transportation and logistics will be presented.